Temperature dependence of 2V angle in biaxial negative and positive nematic lyotropic phases. (2nd November 2019) - Luders, D. D.; Braga, W. S.; Santos, O. R.; Sampaio, A. R.; Kimura, N. M.; Simões, M.; Palangana, A. J.
ABSTRACT: Refractive index measurements and conoscopic images has confirmed the occurrence of biaxial negative ( N B − ) and biaxial positive ( N B + ) nematic phases between the two uniaxial nematic (calamitic − N C and discotic − N D ) phases. These nematic phases are found in a phase diagram line of potassium laurate ( KL ), decanol ( D e O H ), potassium sulfate and water. Biaxial positive ( N B + ) nematic phase is also optically characterized between two uniaxial N D phases in a KL, DeOH, and D 2 O mixture. Temperature dependence of the angles ( 2 V X and 2 V Z ) between two optic axes of ( N B − and N B + ) phases is obtained from refractive index data. The transition point ( N B − − N B + ) characterized by an angle peak corresponds to the change in the biaxial configuration of the optical axes and optical signal of the biaxial nematic phase. The micellar configuration of biaxial nematic phases is discussed as a consequence of our experimental data.